Aciculitin D, a cytotoxic heterodetic cyclic peptide from a Poecillastra sp. marine sponge. (30th July 2022) - Sugawara, Kenji; Kanki, Daichi; Watanabe, Ryuichi; Matsushima, Ryoji; Ise, Yuji; Yokose, Hisayoshi; Morii, Yasuhiro; Yamawaki, Nobuhiro; Ninomiya, Akihiro; Okada, Shigeru; Matsunaga, Shigeki
Abstract: A new cyclic lipopeptide aciculitin D (1 ) was isolated from a Poecillastra sp. marine sponge collected in the deep-sea. The structure of aciculitin D (1 ) was elucidated by spectroscopic analyses and chemical degradation. With regard to amino acid sequence, aciculitin D is different from aciulitin B in one residue substitution of L-Gln for L-Thr. However, absolute configurations of some of the residues are different between the two compounds. Aciculitin D (1 ) shows cytotoxicity against HeLa and HCT-116 cells with IC50 values of 4.5 μM and 1.4 μM, respectively. Graphical abstract: Image 1